Analisis Pemanfaatan dan Penatausahaan Aset Tetap (Tanah) pada Badan Keuangan dan Aset Daerah (BKAD) Kabupaten Manggarai Barat (Jurnal Kendali Akuntansi, 2025)
This study aims to analyze the utilization and management of fixed assets in the form of land at the Regional Finance and Asset Agency (BKAD) of West Manggarai Regency in accordance with the regulations stipulated in Minister of Home Affairs Regulation No. 19 of 2016 and Regulation No. 47 of 2021. The study employs a qualitative approach using primary data obtained through direct interviews and secondary data obtained from documentation related to fixed assets. Data analysis is conducted descriptively to depict the actual conditions of land utilization and asset management in West Manggarai Regency. The results indicate that the utilization of fixed land assets has not been fully compliant with Minister of Home Affairs Regulation No. 19 of 2016, as there are still some vacant lands that have not been utilized. The management of fixed land assets is carried out through three main stages. First, the recording stage has been largely compliant with Regulation No. 47 of 2021, supported by the use of the Regional Government Management Information System (SIMDA) for Regional Property, which facilitates the recording process. Second, the inventory stage is not yet fully compliant because some lands lack ownership documents, such as land certificates, leaving the date and certificate number fields blank. Third, the reporting stage has been conducted in accordance with the regulations, where the Regional Property Reports are compiled hierarchically and submitted both semi-annually and annually. Based on these findings, it is recommended that BKAD West Manggarai Regency improve the utilization of vacant lands and immediately carry out registration and certification processes to ensure the legal status of the land. Further research is expected to explore the management of fixed land assets more comprehensively, including maintenance, supervision, and long-term usage planning to support optimal regional financial management.